Genomic characteristics revealed by targeted exon sequencing of testicular germ cell tumors in Japanese men. (12th October 2020) - Matsumoto, Takashi; Shiota, Masaki; Uchiumi, Takeshi; Ueda, Shohei; Tsukahara, Shigehiro; Toshima, Takahiro; Matsumoto, Shinya; Noda, Nozomi; Eto, Masatoshi; Kang, Dongchon
Abstract : Objective: To investigate the somatic mutation profiles of testicular germ cell tumors in Japanese men. Methods: We analyzed the somatic missense mutation profile of testicular germ cell tumors among 21 Japanese men with seminoma ( n  = 14), pure embryonic carcinoma ( n  = 3) and mixed testicular germ cell tumor ( n  = 4) by targeted next‐generation sequencing of 409 cancer‐related genes covering 1.23 Mb of the genome. Results: We identified a total of 22 missense mutations in 21 primary testicular germ cell tumor samples (0.89 mutations/Mb), of which seven mutations were confirmed to be absent from the germline. KIT:p.Asn822Tyr, KIT:p.Leu576Pro, PIK3CA:p.Glu542Lys and FBXW7:p.Arg505His were statistically and functionally potential. A total of 18 missense mutations were previously unknown in testicular germ cell tumors. PDGFRA amplification from one patient with seminoma was detected. KIT, BCR, PIK3CG, PIK3CA and PDGFRA mutations involved in aberrant signaling of the KIT – PI3K – AKT pathway was detected in 27.3% of detected mutations. Conclusions: The present investigation identified a low mutation rate in testicular germ cell tumors among Asian patients, 18 novel mutations and PDGFRA amplification. Limitations of the present study are the small sample and missing normal DNA for some testicular germ cell tumors.